Home from Away: Challenging Extinction Discourse through the Repatriation of Indigenous Beothuk Human Remains - Daly, Leanne (University of Cambridge, 2023)
From the era of European colonialism of the so-called “New World” to today, the categorisation of certain Indigenous peoples as “extinct”, like the Beothuk of Newfoundland, Canada, has persisted. This discourse of Social Darwinism (where extinction takes place within parts of the human species rather than extinction of the species) has largely been applied uncritically and unquestioningly to such peoples. Literature on “extinct” peoples like the Beothuk comes to be defined by this categorisation and limited by it. This thesis reveals how extinction discourse is not accurate or useful to those on either side of the repatriation process and is reductive and damaging to the understanding of peoples categorised as “extinct”. This is done through critically analysing the discourse of Beothuk extinction through texts (from history books to memorials and museum exhibitions) and tracking the repatriation of remains of two of the last known Beothuk individuals, Nonosabasut and Demasduit, while investigating how those involved in repatriations understand the Beothuk and operate when faced with cases of peoples categorised as “extinct”. Ultimately, the alternative application of the concepts of genocide and social death is proposed as they more appropriately describe what has until now been called “extinction” of Indigenous peoples. Fieldwork support provided by the University Fieldwork Fund, the Anthony Wilkin Fund, and the Holland Rose Fund.